2020
DOI: 10.3389/fphar.2020.01081
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors That May Affect the Effect of Atropine 0.01% on Myopia Control

Abstract: Children respond differently to atropine treatment, and predicting patient factors associated with better myopia control is important. Therefore, we aimed to evaluate factors related to myopia progression in Chinese children treated with atropine 0.01%. This retrospective study included 133 children who were administered atropine 0.01% eyedrops every night for 1 year. Enrolled children were examined at follow-up visits at 3 and 6 months, and 1 year. The primary outcome was clinically significant myopia progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The optimal long-term atropine treatment strategies are currently not established, given that most studies report an active treatment period of only 1 to 2 years. 15,[24][25][26][27][28][29][30][31][32] According to the findings of the ATOM2 study, 4,9 the World Health Organization suggested in 2015 that treatment cessation for 1 year should be considered if good treatment responses are observed after 2 years of continuous therapy, and those who show progression after the 1-year cessation can be offered further treatment. 10 Our results show significant differences in SE and AL between continued treatment and washout subgroups.…”
Section: Continuing Atropine Treatment During the Third Yearmentioning
confidence: 99%
“…The optimal long-term atropine treatment strategies are currently not established, given that most studies report an active treatment period of only 1 to 2 years. 15,[24][25][26][27][28][29][30][31][32] According to the findings of the ATOM2 study, 4,9 the World Health Organization suggested in 2015 that treatment cessation for 1 year should be considered if good treatment responses are observed after 2 years of continuous therapy, and those who show progression after the 1-year cessation can be offered further treatment. 10 Our results show significant differences in SE and AL between continued treatment and washout subgroups.…”
Section: Continuing Atropine Treatment During the Third Yearmentioning
confidence: 99%
“…In the Low-Concentration Atropine for Myopia Progression (LAMP) study, 0.01% atropine, despite its inferior efficacy compared with 0.025% and 0.05% atropine, still showed a 27% and 27.7% reduction in myopia progression 1 and 2 years after treatment, respectively 20,21 . Other studies have also demonstrated the efficacy of 0.01% atropine in treating childhood myopia [22][23][24][25][26][27][28][29][30][31][32][33][34] . However, limited information is available concerning who would benefit most…”
mentioning
confidence: 99%
“…Against the rapid and widespread development of myopia, a series of interventions for myopia control in children have reached high-level evidence, among which low concentration atropine is an effective one ( 13 16 ). This study compared the myopic progression in children treated with 0.01% atropine or not during the 2022 quarantine, and found the myopic progression decelerated in children with continuous medication since the outbreak of the pandemic in February 2022, though two previous studies showed that 0.01% atropine had little effect on myopic progression during the lockdown ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, low-concentration atropine eye drops is recommended and widely used to slow myopic progression ( 13 16 ). Though 0.05% atropine has been proved to be the optimal concentration for myopia control ( 15 , 16 ), it is not commercially available in our country compared with 0.01% atropine which is clinically easy to prescribe in Shanghai.…”
Section: Introductionmentioning
confidence: 99%